Extreme maternal morbidity in the Peruvian Instituto Nacional Materno Perinatal, experience and results - Guevara Ríos, Enrique (2024)
Introduction: Extreme maternal morbidity (EMM) is an indicator for estimating thequality of obstetric care in pregnant or postpartum women with severe morbiditieswho survive because of the care received in obstetric services. Objective: To determinethe causes, dysfunctions and morbidity and mortality indicators of cases of extremematernal morbidity attended at the Instituto Nacional Materno Perinatal between2017 and 2023 and the results of their care. Methodology: We reviewed the medicalrecords of pregnant women with EMM criteria, determining causes, dysfunctions,care and evolution, evaluating the results with morbidity and mortality indicators.Results: In the 1,931 medical records of women with MME, the predominant etiologywas preeclampsia with 911 cases (47.2%) followed by postpartum hemorrhagewith 359 cases (18.6%). The most frequent dysfunctions between 2017 and 2020were hepatic, respiratory and coagulation dysfunctions and, from 2021 onwards,coagulation and cardiac dysfunctions. The MME ratio ranged from 12.7 to 26.1 x1,000 live births. Since 2017, the case fatality indicator is 1.8 maternal deaths (MM) x100 MME cases, and the MME/MM ratio has remained higher than 35 MME cases x 1MM case. The criterion/case ratio in 2023 was 2.2, reflecting the severity of the cases.Conclusion: The good quality of care of the INMP service in MME cases points to thisindicator as a strategy to reduce maternal mortality in the country.